Proposal for the transition and continuity of care from the Intensive Care Unit to the nursing (Research, Society and Development, 2021)
Objective: to propose elements for a model of transition and continuity of care for patients from the Intensive Care Unit (ICU) to the trauma ward. Method: qualitative, exploratory research, carried out with nurses from a trauma hospital in southern Brazil, from May to June 2017, totaling 22 participants. Data were collected through semi-structured interviews, with a vignette, and analyzed by Categorical Thematic Content Analysis, using the MAXQDA® software for data organization. Results: four categories emerged: elements indicative of the exit and entry of the patient in transition from the Intensive Care Unit (ICU) to the infirmary; planning the process of transition and continuity of patient care from the ICU to the ward; implementation of the transition process and continuity of care for the patient from the ICU to the ward; and facilitating elements in the process of continuity of care for patients in transition from the ICU to the ward. The result was a patient-centered model, with the elements for a patient-centered plan for the transition and continuity of care for patients from the intensive care unit to the trauma ward. Conclusion: The creation of professional practices that foster an understanding of transition are crucial strategies for the continuity of care.